Analisis Pendapatan Usahatani Padi Sawah (Oriza Zativa) di Kelurahan Unaasi Kecamatan Anggaberi Kabupaten Konawe - Fanji Fanji; Sarty Syarbiah; Leni Saleh (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This research aims to analyze the income and costs of rice farming in Unaasi Village, Anggaberi District, Konawe Regency and analyze the income of rice farming in Unaasi Village, Anggaberi District, Konawe Regency. The total research sample was 32 people. To answer the first objective, use revenue and cost analysis and to answer the second objective, use income analysis. Analysis results: The amount of income from rice farming in Unaasi Village is IDR. 940,200,000 with an average of Rp. 28,668,750 while the costs incurred were Rp. 761,578,750 with an average of Rp. 6,286,553. The amount of income received by respondent farmers in Unaasi Village is IDR. 201,806,250 with an average of Rp. 6,306,445.